A fast decoding algorithm for space-time block codes - Ke Li; Bin Tang; Jina-yu Yang; Zheng-cong Du (ISCIT 2005 : International Symposium on Communications and Information Technologies 2005 : proceedings : October 12-14, 2005, Beijing, China, 2005)
This paper presents a low complexity algorithm for the decoding of space-time block codes. The new decoding algorithm arrives at the same decision with much less complexity, using constellation space partitioning. Simulation shows that the proposed decoding algorithm cuts down the computation complexity of decoding from nearly 80% to more than 95%, comparing with the original decoding algorithm, and without any performance loss.